Knowledge, attitudes and behaviors of medical faculty students about family medicine (Annals of Medical Research, 2021)
Aim: It was aimed to determine the knowledge levels of medical faculty studentsabout the family medicine discipline, their approach to primary care, their interest in the family medicine career and the factors affecting it.Material and Methods: The universe of our study was 713 people, and the sample size was calculated as 250 people in 5% margin of error and 95% confidence interval. A questionnaire included 62 questions which were aboutthe knowledge, attitudes and behaviors of medical students about family medicine.In the variables with normal distribution, the comparisons of the two groups were carried out with two independent samples t test.In non-normally distributed variables, comparisons of the two groups were examined by Mann-Whitney test.Categorical variables were examined with Chi-Square test. Statistical significance was accepted as p 0.05.The data were evaluated in IBM SPSS version 22 program.Results: 50.4% of the participants were male, 49.5% were female and the mean age was 22.00 ± 2.46. The rate of those who had never been to a family physician in the last year was 41.1%. 28.5% of theparticipants stated that they mostly applied tothe family physician except to the emergencies and the most common reason for going to the family physician (63.8%) was new health problems. The majority of the participants (79.3%) wanted the referral system to be implemented. When the answers of the participants about the duties of family physicians were examined, the three most common known propositions were : ”Family physician vaccinates infancy, childhood and adulthood” (90.2%), ”In the practice of family medicine, dressing, injection and wound care services are provided” (%87.0), and “Family physician can give health report”(%84.1).Conclusions: The majority of medical faculty students apply to secondary or tertiary health care providers when they experience any health problems. The fact that almost half of the participants stated that they have never been to be a family physician in the last year shows numerically how grave the situation is. First of all, people should be informed to adopt family health centers as the first health institution to be consulted.